Anionic Oligothiophenes Compete for Binding of X‐34 but not PIB to Recombinant Aβ Amyloid Fibrils and Alzheimer's Disease Brain‐Derived Aβ. Issue 51 (3rd November 2016) - Bäck, Marcus; Appelqvist, Hanna; LeVine, Harry; Nilsson, K. Peter R.
Abstract: Deposits comprised of amyloid‐β (Aβ) are one of the pathological hallmarks of Alzheimer's disease (AD) and small hydrophobic ligands targeting these aggregated species are used clinically for the diagnosis of AD. Herein, we observed that anionic oligothiophenes efficiently displaced X‐34, a Congo Red analogue, but not Pittsburgh compound B (PIB) from recombinant Aβ amyloid fibrils and Alzheimer's disease brain‐derived Aβ. Overall, we foresee that the oligothiophene scaffold offers the possibility to develop novel high‐affinity ligands for Aβ pathology only found in human AD brain, targeting a different site than PIB. Abstract : The battle for amyloid deposits : A variety of anionic oligthiophenes efficiently displaced X‐34, a Congo Red analogue, but not Pittsburgh compound B (PIB) from deposits comprised of amyloid‐β (Aβ). Furthermore, for tetrameric oligothiophenes, the nature of the α‐terminal chemical moiety was demonstrated to be a key determinant for efficient displacement of X‐34. Overall, we foresee that oligothiophene scaffolds offer the possibility to develop novel high‐affinity ligands, targeting Aβ pathology only found in human Alzheimers diseased brain.